PENGEMBANGAN OLAHAN TOMAT ENREKANG DALAM BENTUK KURMA TOMAT (KARAKTERISTIK KURMA TOMAT) - Laga, Amran; Langkong, Jumriah; Muhpidah, .; Fitri, .; Wakiah, Nurul (Jurnal Dinamika Pengabdian, 2018)
Tomatoes are one of the common fruit that is known to public. It has high availability and easy to be found in the market. Fresh tomatoes processing is still limited in some product meanwhile tomatoes are easily damaged and have a short-lived due to its high water content and presence of physical damages.  The processing of tomatoes into the product with lower water content such as dates (candied) is one of the methods to prolong shelf life and prevent it from the damage. The purpose of this paper is to increase the economic value of tomatoes through the processing into the tomatoes dates. This research is expected to provide benefits for farmers and processing industries, primarily engaged in the processing of vegetables and fruits, to support the development of agro-industries in rural areas. Making tomatoes dates begins with the sorting process, adding sugar to the ratio of tomatoes and sugar 2:1, then cooking on low heat and drying for 12 hours with observations every 3 hours. Tomato dates are divided into blanching and non-blanching tomatoes. It was concluded that blanching tomatoes is the best treatment with, water content of 13.8%, pH 5.32 and can maintaned total vitamin C of 60.25% during drying process. Organoleptic test showed that the panelists preferred the blanching tomatoes based on color, aroma, texture and taste.Keywords: Tomatoes, Tomato Dates, Blanching, Non-blanching